Characteristics of Heavy Metal Ion Adsorption by Silty Mudstones in Coal Mine Goafs. (12th February 2020) - Yao, Qiang-ling; Xia, Ze; Tang, Chuan-jin; Zhu, Liu; Wang, Wei-nan; Chen, Tian; Tan, Ying-ming
Abstract : Coal mine goafs can be used to store and purify mine water; therefore, they are important for mitigating the environmental impact of mining on ecologically fragile areas in Western China. Coal gangue in goafs can reduce turbidity, suspended matter, total hardness, and chemical oxygen demand (COD) in mine wastewater. Because gangue in goaf areas is rich in clay minerals, they serve as ion exchange sites. We investigated the adsorption of heavy metal ions by silty mudstones in the Ulan Mulun mine. The adsorption kinetics and isothermal adsorption characteristics of four heavy metal ions, i.e., Pb(II), Cd(II), Cr(III), and Mn(II), were investigated using batch experiments. Under a pH of 6.75 and temperature of 20°C, the adsorption capacity of silty mudstone particles (<74 μ m) was 6.3012 g, 1.5701, 1.2571, and 1.3729 mg/g for Pb(II), Cd(II), Cr(III), and Mn(II), respectively. Based on the experimental results, quantitative relationships between the adsorption quantity per unit of rock surface and the equilibrium concentration of heavy metals in solution were developed using Langmuir, Freundlich, and D–R equations. The relationships were used to obtain the equilibrium concentration of the solution. Finally, the ratio of the f value of the water-rock contact area in the goaf to the water volume was calculated and analyzed. The f value was inversely proportional to the average vertical opening of gaps between gangues in the goaf. The adsorption rate functions for Pb(II), Cd(II), Cr(III), and Mn(II) in the goaf were obtained, and the corresponding adsorption capacities were calculated. The adsorption capacities were controlled by the f value and adsorption properties of the gangue. These results can be used in future studies on mine wastewater treatment.